Ulrich von Hutten's Partisanship in the Reuchlin Controversy (1514-1519): Determining Functions of "Invectivity" in Early Sixteenth-Century German Humanism - Dröse, Albrecht (Journal of Early Modern Christianity, 2023)
At the beginning of the sixteenth century, the controversy around the Hebraist Johannes Reuchlin rather quickly developed from a mere scholarly dispute into a mass media event. The German humanists played a large part in this, countering his supposed opponent, the Jewish convert Johannes Pfefferkorn, with a multitude of elaborate invectives, and acting as a vituperative community. Ulrich von Hutten participated particularly eagerly in the anti-Pfefferkorn discourse and was heavily involved in its satirical climax, the Epistolae obscurorum virorum . The concept of "invectivity" can provide a new heuristic focus for questions related to the function, effect and group dynamics of humanist invectives, especially in the example of Hutten, and help to better understand the complexity of this European media event.